(untitled) (Biological Sciences - PJSIR, 2000)
Calophyllum inophyllum Linn, is a beautiful ornamental tree with long stalked white flowers at the ends of the branches. Its glossy broad elliptic leaves with numerous parallel lateral veins are most distinctive. C. inophyllum belongs to Guttiferae which are trees or shrubs occurring chiefly in the tropics. They have simple opposite leaves, often with translucent lines or dots. All of the Nigerian species yield resinous juice when slashed and most of them have distinctly whorled branches (Keay et al 1966).